The Classification of Arabic Dialects: Traditional Approaches, New Proposals, and Methodological Problems - Bettega, Simone; Morano, Roberta (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The question of how to classify the different varieties of spoken Arabic is a long-standing problem in the fields of Arabic and Semitic linguistics, and it has been addressed by several authors and from a number of different perspectives. This collection of articles represents a further contribution to the vast collective effort of attempting to more effectively assess, organize, and understand the varieties of spoken Arabic, applying a classification of Arabic dialects in the broadest possible sense. The authors who contribute to this volume tackle this issue by examining varieties spoken from the Maghreb to the Mashreq and employing various approaches and perspectives, e.g., diatopic and diachronic, syntactical, and typological.